Direct Cooperation Has Begun: Some Remarks on the Judgment of the ECJ on the OMT Decision of the ECB in Response to the German Federal Constitutional Court's First Request for a Preliminary Ruling. Issue 4 (1st September 2015) - Simon, Sven
Abstract : By its first request for a preliminary ruling, the German Constitutional Court aired its doubts about the lawfulness of the Outright Monetary Transactions (OMTs) program. In this article it is argued that the ECB's pledge in the summer of 2012 to do "whatever it takes" to safeguard the monetary policy transmission mechanism in all countries of the euro area by buying government bonds was generally compatible with EU law. However, it is argued that there is some potential for the ECB to infringe the Treaty on the Functioning of the European Union (TFEU) while acting according to this announcement. The peculiarity of the situation, the author argues, is that we might be dealing with a "self-fulfilling prophecy" in that the ECB announces a particular policy, which might not be compatible with EU law, but the act announced, will never take place because the political problem would have been resolved by the measure previously announced. The critical question in this scenario refers to how a court should react to such a situation. The author argues that a court in such a situation has to show the legal limits of the particular institution, but neither the ECJ nor the German Constitutional Court may replace the central banks' task to maintain financial stability. Finally, a comment is given on how the German Constitutional Court will react to the ECJ's decision in that case.